GENESIS OF THE ECONOMIC RELATIONS IN THE SOCIAL AND CULTURAL FIELD OF RUSSIA - S.A. BEYGULENKO (Advanced Engineering Research, 2010)
The article contains the description of the basic forms of the economic relations in the social and cultural field (SCF) which were formed in the Soviet and post- Soviet period and are being developed in the modern economy of Russia. The knowledge of methodology of the shaping and development of the economic relations in social  and cultural field is impossible without the knowledge of the genesis of these relations.